2007
DOI: 10.1038/sj.ki.5002241
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcification: Contribution of parathyroid hormone in renal failure

Abstract: Hyperphosphatemia is a driving force in the pathogenesis of vascular calcification (VC) and secondary hyperparathyroidism associated with renal failure. To test for the possible contribution of parathyroid hormone (PTH) to cardiovascular calcification, we removed the parathyroid glands from rats but infused synthetic hormone at a supraphysiologic rate. All rats were pair-fed low, normal, or high phosphorus diets and subjected to a sham or 5/6 nephrectomy (remnant kidney). Control rats were given a normal diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
1
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 29 publications
5
104
1
10
Order By: Relevance
“…16 The causal relationship between hyperparathyroidism and vascular calcification depends, at least in part, on the bone-vascular axis. 17 Therefore, we examined the effects of L-Lys on the femora. Both transverse sections of the femoral diaphyses ( Figure 6A) and threedimensional reconstructed images of the distal femora ( Figure 6B) demonstrated that the rats in group LP had intact femora, whereas the rats in groups Ade and Gly had osteoporotic femora.…”
Section: L-ly Protected the Femora From Osteoporotic Changes In Adenimentioning
confidence: 99%
“…16 The causal relationship between hyperparathyroidism and vascular calcification depends, at least in part, on the bone-vascular axis. 17 Therefore, we examined the effects of L-Lys on the femora. Both transverse sections of the femoral diaphyses ( Figure 6A) and threedimensional reconstructed images of the distal femora ( Figure 6B) demonstrated that the rats in group LP had intact femora, whereas the rats in groups Ade and Gly had osteoporotic femora.…”
Section: L-ly Protected the Femora From Osteoporotic Changes In Adenimentioning
confidence: 99%
“…A Mönckeberg-arteriosclerosis esetén pedig a mineralizáció az érfal mediarétegében zajlik. A hosszú időn át fennálló magas szérumfoszfát-koncentráció növeli a kalcifi laxis előfor-dulását, amely a kiserek falának kalcifi kációjával járó, éle-tet veszélyeztető szövődmény [11].…”
Section: A Krónikus Vesebetegség Során Megjelenő áSványi-és Csontanyaunclassified
“…In questi ultimi, è stato descritto un ispessimento dell'intima e della media senza la marcata tendenza alla calcificazione tipica della CKD ed è stata, inoltre, registrata la regressione delle alterazioni cardiache dopo la paratiroidectomia. Il PTH, può, pertanto, innescare il processo di calcificazione arteriosa indipendentemente dalla presenza di iperfosforemia (29). Mentre questi risultati hanno evidenziato i risvolti negativi sul deterioramento arterioso secondario all'iperparatiroidismo, altri studi in diversi modelli animali hanno osservato un effetto benefico dello stesso, sulla funzione miocardica, sul tono arterioso, sulla contrattilità cardiaca e sulla vasodilatazione (30)(31)(32).…”
Section: Sodio-potassiounclassified